2014
DOI: 10.1002/prot.24625
|View full text |Cite
|
Sign up to set email alerts
|

Molecular simulations of β-lactoglobulin complexed with fatty acids reveal the structural basis of ligand affinity to internal and possible external binding sites

Abstract: The interaction of saturated fatty acids of different length (C8:0 to C18:0) with β-lactoglobulin (βLG) was investigated by molecular dynamics simulation and docking approaches. The results show that the presence of such ligands in the hydrophobic central cavity of βLG, known as the protein calyx, determines an enhancement of atomic fluctuations compared with the unliganded form, especially for loops at the entrance of the binding site. Concerted motions are evidenced for protein regions that could favor the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 52 publications
4
17
0
1
Order By: Relevance
“…The molecule docking and dynamic simulation of interaction between OA and β-LG was performed as per Evoli et al (2014) and Trott and Olson (2010) with slight modifications. The crystal structure of β-LG (PDB ID: 3NPO) was downloaded from the RCSB Protein Data Bank (http: / / www .rcsb .org/ pdb).…”
Section: Molecule Docking and Molecule Dynamic Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecule docking and dynamic simulation of interaction between OA and β-LG was performed as per Evoli et al (2014) and Trott and Olson (2010) with slight modifications. The crystal structure of β-LG (PDB ID: 3NPO) was downloaded from the RCSB Protein Data Bank (http: / / www .rcsb .org/ pdb).…”
Section: Molecule Docking and Molecule Dynamic Simulationmentioning
confidence: 99%
“…Evoli et al (2014) also reported that the palmitic acid in site 3 migrated from its starting position during the simulation, indicating that the site 3 was not a reliable binding sites for fatty acid. For unsaturated OA in site 1, the starting U-shape conformation obtained from docking simulation was extended after molecule dynamic simulation ( Figure 6, represented in blue), and the carboxylate group of the OA interacted with polar residues Lys60, Glu62, and Lys69 by electrostatic interactions and a hydrogen bond that agrees well with the results obtained by Loch et al (2013) and Evoli et al (2014). The outer surface site 2 was a small protein pocket consisting of residues Tyr20, Tyr42, Ser21, Glu157, and His161, which was also identified by molecular docking for epigallocatechin-3-gallate (Wu et al, 2011) and palmitic acid (Evoli et al, 2014).…”
Section: Changes Of Surface and Total Sh Content Of β-mentioning
confidence: 99%
“…Unfortunately, microscopic details concerning the dynamics of the lipid binding are currently not easily accessible to the experiment. Molecular dynamics (MD) 1 represents an interesting tool to tackle this issue [13,14] and has already been successfully employed in a few cases [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…When the calyx is occupied by ligands, the lid has been detected only in the open conformation [23]. Computational studies using docking, as well as molecular dynamics, have been useful in the characterization of BLG's atomic interactions with ligands [12,15,[17][18][19][20], producing data in close accord with those from thermodynamic and crystallographic experiments, and demonstrating that it is possible to predict binding to this protein by computational methods. Here, we used docking and molecular dynamics to predict if pesticides of common use bind to cow's milk BLG, and to computationally explore whether this protein could act as a pesticide carrier and potentially contribute to human exposure through dairy.…”
Section: Introductionmentioning
confidence: 92%
“…Each BLG monomer consists of 162 residues (18.3 kDa), folded into eight-stranded antiparallel β-sheets that form a hydrophobic binding pocket called the calyx (shown in Figure 1 and Figure S1), flanked by an α-helix [16]. BLG binds to a variety of nutrients like fatty acids, peptides, sugars and some vitamins ( Figure S2) in at least two different binding sites, the most prominent of which is the calyx [15,17,18] (the second site is formed in the interphase between two BLGs when they dimerize [15], and will not be explored here). The affinity for the known hydrophobic ligands in the calyx is in the micromolar range [19].…”
Section: Introductionmentioning
confidence: 99%